Lian Hua Qing Wen Capsules, a Potent Epithelial Protector in Acute Lung Injury Model, Block Proapoptotic Communication Between Macrophages, and Alveolar Epithelial Cells - Li, Qi; Ran, Qingsen; Sun, Lidong; Yin, Jie; Luo, Ting; Liu, Li; Zhao, Zheng; Yang, Qing; Li, Yujie; Chen, Ying; Weng, Xiaogang; Wang, Yajie; et al. (Frontiers in Pharmacology, 2020)
Besides pathogen evading, acute Lung Injury (ALI), featuring the systematic inflammation and severe endothelial damages, is widely believed to be the central noninfectious factor controlling the progression of infectious diseases. The interaction unit consisting of ER-stressed macrophages and the alveolar epithelial cells has recently revealed as the therapeutic basis targeting ALI. Lian Hua Qing Wen capsule（LHQW） is the most effective and commonly-used clinical formula in treating respiratory infection for thousands of years in China. However, little is known about its relevance with ALI, especially its protective role against ALI-induced alveolar tissue damages.Aiming to evaluate its contribution in antibiotics-integrating therapies, this study pharmacologically verified whether LHQW could alleviate lipopolysaccharide (LPS)-induced ALI and explore its potential mechanisms in maintaining the physiology of Macrophage-Epithelial unit. In ALI mouse model in vivo, the pathological parameters, including the anal temperature, inflammation condition, lung edema, histo-pathological structures, have all been systematically analyzed. Results consistently supported the effectiveness of the combined strategy for LHQW and low-dose Antibiotics.Furthermore, we established the macrophages-alveolar epithelial cells co-culture model and firstly proved that LHQW inhibited LPS-induced ER stress and TRAIL secretion in macrophages, thereby efficiently protected epithelial cells against TRAIL-induced apoptosis. Mechanistically, results showed that LHQW significantly deactivated NFkappaB and reversed the SOCS3 expression in inflamed macrophages. Furthermore, we proved that the therapeutic effects of LHQW was highly dependent on JNK-AP1 regulation. In conclusion, our data proved that LHQW is an epithelial protector in ALI, 3 implying its promising potential in antibiotic alternative therapy.